MODELING OF HOT OIL LEAKAGE AT REGENERATION GAS HEATER ON DEHYDRATION PROCESS OF NATURAL GAS LIQUIFIED EXTRACTION (NGLE) GAS PLANT - Azani, Yung; Armila, Armila; Arief, Rudi Kurniawan (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2022)
The regeneration process in saturated dehydrator after working to drying the gas in the dehydration unit in the Natural Gas Liquified Extraction (NGLE) plant. This process is through the heating dehydrator process by flowing the regeneration gas into the dehydrator slowly (rump up temperature) until it reaches the heating temperature,and then holding the condition. Its condition is in accordance with the engineering design and followed by a rump down temperature which the dehydrator will be cooled down and ready for the dehydration process. This regeneration process works automatically in accordance with the engineering design which runs following the logic control that has been implemented into the Distributed Control System (DCS) in the Control Room. All order in DCS to obtain gas that has been moisture limited value which is allowed to be extracted. Regeneration gas was taken from the heat exchange between hot oil and regeneration gas in the regeneration gas heater package. This operation happend when the rump up temperature leaks the hot oil in the flange fitting of the regeneration gas heater package, its causes oil spillage (engineering design standart operation procedur). Its analysis case assumed the leakage is caused by thermal shock in the fittings of regeneration gas heater package in 2 % hot oil supply. To eliminate the thermal shock, a simulation of new models engineering design is initial by opening of the hot oil supply to the regeneration gas heater was changes with increasing its opening during stand-by conditions from 2% with a temperature at 45.72Â°C to 5% with a temperature at 51.61C in the Distributed Control System (DCS) logic control. The results goals with this implementation are no more hot oil leaks occur in the regeneration gas heater package. New models engineering design is stopping hot oil spillage, and maintaining operational continuity without having to spend money on repairing the regeneration gas heater package. process run in new models of engineering design, and this model becomes the new standard operating in start-up and commissioning plant process.